The Effectiveness of Strategy-Based Instruction (SBI) To Teach Writing - Mukminatus Zuhriyah (Peneliti.net, 2022)
Writing is assumed as a very complicated skill among other skills. Students’ low motivation and students’ low knowledge of writing as well as inappropriate teacher’s teaching and learning strategy contribute to students’ low writing score. The appropriate teacher’s strategy can motivate the students to practice writing more and more. That is why this research applied strategy-based instruction (SBI) as one of the alternatives in teaching and learning writing. This was a pre-experimental research with one group pretest and posttest design, which was generally to know whether or not strategy-based instruction (SBI) was effective for teaching writing and specifically to find out the students’ ability in writing before and after SBI was applied. This research used total sampling. One class consisting of thirty students became the sample. The data were from writing test scores of pretest and posttest. The average score of posttest (74.6) was higher than that of pretest (69.5). Then, paired sample t-test was used to analyze those scores with the result that sig (2-tailed) 0.00 was lower than 0.05. It means that the average score of pretest differs significantly from that of posttest. Thus, it can be said that SBI is effective for teaching writing.